Systematic Literature Review: Does Realistic Mathematics Education Approach Enhance Mathematical Literacy? - Paradesa, Retni; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Darmawijoyo, Darmawijoyo (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2025)
Realistics Mathematics Education (RME) is an instructional approach that emphasizes the use of real-world problems and situations in mathematics teaching. This method is believed to significantly enhance students' mathematical literacy, which is crucial for their academic and everyday problem-solving skills. This systematic literature review aims to investigate the impact of RME on students' mathematical literacy by synthesizing existing research findings. A systematic review design was employed, focusing on studies that explore the relationship between RME and mathematical literacy. The Scopus database was utilized for bibliometric analysis, with the search term "mathematical literacy" restricted to article titles. Data extracted included author names, citation counts, titles, publication years, sources, publishers, and document types. The analysis revealed approximately total of 200 publications related to mathematical literacy were found with a total of 10,817 citations, resulting in an average of 54.1 citations per article, indicating a substantial body of research on this topic. Notable trends included the integration of computer-mediated learning and various pedagogical models. The findings suggest that RME is an effective pedagogical approach that promotes students' mathematical literacy through authentic and contextualized learning experiences. This review highlights the necessity of developing educational materials and teaching strategies that prioritize mathematical literacy, thereby enhancing students' proficiency in mathematics and preparing them for real-world applications.